Analisis Bibliometrik Publikasi Perkembangan Artificial Intelegent (AI) dalam Dunia Pendidikan - Arianti, Juli; Oktaviani, Mutiya; Najdah T, Najdah T; Sinambela, Yohannes Putra Perkasa (AKADEMIK: Jurnal Mahasiswa Humanis, 2024)
The aim of this research is to examine the development of publications related to Artificial Intelligence (AI) in the world of education. This research uses bibliometric analysis with the keyword "Artificial intelligence in education" from 2020-2024. The research results show that there are 970 scientific articles that appear according to keywords and there is an increase in research every year. Based on visualization analysis from VOSViewer, it shows that the most studied theme is Artificial intelligence technology which discusses teaching, educational institutions, learning, performance, higher education, abilities, ChatGpt, etc. This research provides an overview for researchers and readers in developing relevant research topics.